PENINGKATAN KEMAMPUAN GURU SMP DALAM PEMBELAJARAN DENGAN METODE PROJECT BASE LEARNING (PBL) PADA MASA PANDEMIK - Salfila Juliana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The current covid-19 pandemic has an impact on every aspect of life, including the education aspect. It will also influence the process of improving teachers' performance. In this case, teachers are greatly affected by the current pandemic because all forms of teaching and learning processes, training activities, seminars, and many other activities are forced to stop during the current pandemic. Meanwhile, teachers must attend training or seminars to improve their teaching ability and to develop various learning methods. This research was conducted at nine public and private junior high schools in Kabupaten Bengkalis. The subjects in this study were teachers who taught at the schools. The purpose of this research was to improve teachers' ability in the learning process by using a project-based learning method during the covid-19 pandemic. The results obtained that the students' learning outcomes at seven schools were in the very good category and only two schools obtained students' learning outcomes in the poor category. This study concluded that 77.7% of students from nine high schools reached the minimum achievement criteria, which was categorized as very good. Thus, the implementation of the base learning project in 9 schools in Kabupaten Bengkalis is quite effective.